Uncontrolled blood sugar tends to increase prevalence of dermatomycosis in diabetic type 2 patients - Surja, Sem Samuel; Hermawan, Melyawati; Wijaya, Meiliyana; Pramanta, Pramanta; Yolanda, Hanna (Faculty of Medicine, Trisakti University, 2018)
Background The prevalence of type 2 diabetes mellitus (DM) is increasing. Diabetic patients have a higher risk of getting dermatomycosis. Dermatomycoses, although a common health problem amongst DM, is often misdiagnosed and consequently undertreated. Studies on the association between dermatomycosis and type 2 diabetes are lacking, especially in Indonesia. Therefore, the aim of this study was to determine the prevalence, etiology, and association of dermatomycosis with diabetic control of type 2 DM. MethodsA cross-sectional study was performed involving 87 subjects with type 2 DM. Demographic and clinical data, including age, sex, and blood glucose level, were collected. If a dermatomycosis lesion was found, a specimen would be taken for identification. Determination of serum glucose level was conducted using Roche c111 analyzerÂ®. Statistical analysis was performed with the chi-square test and Kolmogorov-Smirnov two-independent sample test.ResultsSeventeen (19.55%) subjects had dermatomycosis. The predominant age group affected was 51 - 60 years (42.4%). The number of clinically apparent dermatomycosis was greater in the uncontrolled than in the controlled blood sugar group, but the difference was statistically not significant (p > 0.05). The lesions were mostly found on the nails (74%) and the most common etiology was candida (50%) followed by dermatophyte (25%) and non-dermatophyte molds (25%). ConclusionUncontrolled blood sugar tends to increase the risk of dermatomycosis in type 2 DM patients. Fungal skin infections are common in type-2 DM patients, especially in those with poor glycemic control.